Higher levels of oxidative balance score linked to lower risk of gallstones: findings from the 2017–2020 National Health and Nutrition Examination Survey - Xiong, Ting; Chen, Zhonghuo; Yi, Jianwei; Yu, Taozhi; Wang, Kai (Frontiers in Nutrition, 2025)
Background and objectiveThe Oxidative Balance Score (OBS) has been linked to various chronic diseases; however, its association with gallstone prevalence remains underexplored. This study aimed to investigate the relationship between OBS and gallstone risk.MethodsThis cross-sectional study utilized data from the National Health and Nutrition Examination Survey (NHANES) conducted from 2017 to March 2020. Weighted logistic regression models were applied to examine the association between OBS and the prevalence of gallstones, complemented by subgroup and sensitivity analyses. Restricted cubic spline (RCS) was used to investigate the nonlinear association between OBS and the prevalence of gallstones.ResultsA total of 5,382 participants were included, among whom 592 reported a history of gallstones. After adjusting for confounding factors, a significant negative association was observed between OBS and gallstone prevalence (quartile 4 vs. quartile 1: odds ratio [OR] 0.63, 95% confidence interval [CI] 0.43–0.90, p = 0.019). The RCS analysis further supported a negative linear relationship between OBS and gallstone risk (nonlinear p = 0.149). The findings of the subgroup analyses exhibited considerable consistency.ConclusionThis study identified a significant negative linear association between OBS and gallstone risk, suggesting that higher OBS levels are associated with a reduced likelihood of gallstone formation.